Gulliver's travels - Swift, Jonathan, 1667-1745. (New York : Dodd, Mead, 1950)
The voyages of an Englishman carry him to such strange places of Lilliput, a land of people six inches high, Brobdingnag, a land of giants, and Glubbdubdrib, an island of sorcerers
Pt. I. A voyage to Lilliput. -- Pt. II. A voyage to Brobdingnag. -- Pt. III. A voyage to Laputa, Balnibarbi, Luggnagg, Glubbdubdrib, and Japan. -- Pt. IV. A voyage to the country of the Houyhnhnms
Keywords: Voyages, Imaginary -- Fiction; Fantasy fiction; Fantastic fiction; Satire; Action and adventure fiction; Satirical literature